Lymphoma Presenting as Acute-Onset Dysphagia - Daniel B. Simmons; Andrew W. Bursaw (Case Reports in Neurological Medicine)
A 61-year-old man with recent Bell’s palsy developed acute vocal cord paralysis causing severe dysphagia. CSF analysis showed elevated protein and a normal cell count; contrast-enhanced MRI of the brain was normal. He was treated with IVIG for a presumed bulbar-variant AIDP and gradually improved. Six months later, the patient developed rapidly progressive hearing loss and vestibular dysfunction. Repeat MRI revealed bilateral enhancement of the eighth cranial nerves and a hypercellular mass in the left temporal lobe. Biopsy of the mass confirmed the diagnosis of diffuse large B-cell lymphoma. Lymphomatous invasion of the cranial nerves should be considered in cases of relapsing cranial neuropathies.